2023
DOI: 10.3390/biom13030506
|View full text |Cite
|
Sign up to set email alerts
|

p53 Function and Dysfunction in Human Health and Diseases

Abstract: The p53 protein is a sequence-specific DNA-binding transcription factor that, in response to stressful stimuli, regulates gene expression related to multiple cellular functions including, but not limited to, cell cycle arrest, cell apoptosis, cell growth, DNA repair, cell metabolism, and the immune response [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…At the same time, the activated P53 protein can upregulate the pro-apoptotic p53/AMPK pathway, which is a classical signaling pathway that regulates autophagy [ 31 ]. It has been found that p53 exists widely in the cytoplasm and nucleus and has bidirectional regulation during autophagy [ 32 ]. The P53 protein can activate the AMPK subunit to regulate cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the activated P53 protein can upregulate the pro-apoptotic p53/AMPK pathway, which is a classical signaling pathway that regulates autophagy [ 31 ]. It has been found that p53 exists widely in the cytoplasm and nucleus and has bidirectional regulation during autophagy [ 32 ]. The P53 protein can activate the AMPK subunit to regulate cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that protein domain mutations can potentially be prognostic or predictive biomarkers and treatment responses. For example, the L2 and L3 zinc-binding domains and DNA-binding domain of the TP53 gene are linked to patient poor prognosis and resistance to radiotherapy and chemotherapy in most cancers [ 116 , 124 ]. Similarly, mutations in kinase and helical domains in the phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) have been found in a variety of malignancies, including breast, ovarian, endometrial, and colorectal cancers, and have been linked to a poor prognosis as well as resistance to immunotherapy and targeted treatments [ 125 ].…”
Section: Clinical Relevance Of Protein Domain Mutationsmentioning
confidence: 99%